Figuring resurrection: Joseph as a death & resurrection figure in the Old Testament & Second Temple Judaism - Pulse, Jeffrey (Studies in Scripture & biblical theology, 2021)
"Toward the end of Genesis, the narrative slows down to tell the story of Joseph. There is no dispute that Joseph's story is unique, but why does it deserve such focused attention? And how does this story relate to the rest of Genesis? In Figuring Resurrection, Jeffrey Pulse presents the view that Joseph is a death-and-resurrection figure. A close literary reading of Genesis 37-50 reveals that Joseph's story is one of rejection and restoration, descent and ascent, condemnation and exaltation, exile and return, death and resurrection. Far from a lengthy diversion, Joseph's story of 'death and resurrection' plays an important role in the theology of Genesis and later Second Temple Jewish literature. Figuring Resurrection has implications for our understanding of Joseph's narrative, the book of Genesis, Hebrew thinking on the afterlife, and typology" --